Effects of some environmental conditions on the response of birch bark to wounding - Romakkaniemi, P.; Poteri, Marja (Verlag Paul Parey, 1987)
A histological study was carried out on the process of wound-healing in the bark of Betula pendula after treatment at various temperatures and in the bark of B. pendula and B. pubescens after water stress. Low temperature inhibited phellogen restoration in B. pendula. Wound-healing was delayed in B. pendula when exposed to flooding and drought, and in B. pubescens under drought., The response of B. pendula was faster than that of B. pubescens.
Keywords: forest protection; Betula; bark; plant diseases; resistance to injurious factors; Betula pendula; Betula pubescens